ROS-triggered endothelial cell death mechanisms: Focus on pyroptosis, parthanatos, and ferroptosis - Zheng, Dongdong; Liu, Jia; Piao, Hulin; Zhu, Zhicheng; Wei, Ran; Liu, Kexiang (Frontiers in Immunology, 2022)
The endothelium is a single layer of epithelium covering the surface of the vascular system, and it represents a physical barrier between the blood and vessel wall that plays an important role in maintaining intravascular homeostasis. However, endothelial cell death can cause vascular barrier disruption, vasoconstriction and diastolic dysfunction, vascular smooth muscle cell proliferation and migration, inflammatory responses, and thrombosis, which are closely associated with the progression of several diseases, such as atherosclerosis, hypertension, coronary atherosclerotic heart disease, ischemic stroke, acute lung injury, acute kidney injury, diabetic retinopathy, and Alzheimer's disease. Oxidative stress caused by the overproduction of reactive oxygen species (ROS) is an important mechanism underlying endothelial cell death. Growing evidence suggests that ROS can trigger endothelial cell death in various ways, including pyroptosis, parthanatos, and ferroptosis. Therefore, this review will systematically illustrate the source of ROS in endothelial cells (ECs); reveal the molecular mechanism by which ROS trigger pyroptosis, parthanatos, and ferroptosis in ECs; and provide new ideas for the research and treatment of endothelial dysfunction-related diseases.